Pore Engineering in Carbon Monoliths Through Soft Templating, In Situ Grown Graphene, and Post-Activation for CO2 Capture, H2 Storage, and Electrochemical Capacitor - Madhav P. Chavhan; Moomen Marzouki; Mouna Jaouadi; Ouassim Ghodbane; Gabriela Zelenková; Miroslav Almasi; Monika Maříková; Petr Bezdicka; Jakub Tolasz; Natalija Murafa (Nanomaterials, 2025)
Controlled porosity with precise pore sizes in carbon monoliths (CMs) is crucial for optimizing performance in electrochemical energy storage and adsorption applications. This study explores the influence of porosity in CMs, developed from polymer precursors via the sol–gel route, employing soft templating, in situ graphene growth, and post-activation. The effects on CO2 and H2 sorption and electrochemical capacitor (EC) performance are analyzed. Graphene is successfully grown in situ from graphene oxide (GO), as confirmed by several characterization analyses. The amount of GO incorporated influences the crosslink density of the polymer gel, generating various pore structures at both micro- and mesoscales, which impacts performance. For instance, CO2 capture peaks at 5.01 mmol g−1 (0 °C, 101 kPa) with 10 wt % GO, due to the presence of wider micropores that allow access to ultramicropores. For H2 storage, the best performance is achieved with 5 wt % GO, reaching 12.8 mmol g−1 (−196 °C, 101 kPa); this is attributed to the enlarged micropore volumes between 0.75 and 2 nm that are accessible by mesopores of 2 to 3 nm. In contrast, for the ECs, lower GO loadings (0.5 to 2 wt %) improve ion accessibility via mesopores (4 to 6 nm), enhancing rate capability through better conduction.